Pemilihan Kabel Instalasi Listrik Untuk Bangunan Gedung Berdasarkan Kualitas Tahanan Isolasi - Irman Irman; Latifah Latifah; Ruskardi Ruskardi; Muh Sulkhan Arief (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2022)
The building fire in Pontianak was the result of an electrical short circuit or an electric current, namely the connection between a live conductor and a neutral conductor. Where the electrical installation cables used are generally NYM and NYA cables. NYM and NYA cables must be of good quality. This is related to the safety of buildings against fire hazards due to short circuits of electrical cables. For this reason, research is needed in the form of measuring cable insulation resistance to ensure the quality and feasibility of several cable brands on the local market in Pontianak. Based on the measurement results on the five test samples, each cable NYM 3 x 2.5 mm2, NYM 2 x 2.5 mm2 and NYA 2.5 mm2, it was found that the NYM cable was 3 x 2.5 mm2 (sample A), NYM cable 2 x 2 .5 mm2 (Sample A) and 2.5 mm2 NYA Cable (sample B) have the highest insulation resistance of the cable sheath compared to 4 (four) other samples, namely 25,010 M Ohm (NYM 3 x 2.5 mm2), 25,425 M Ohm ( NYM 2 x 2.5 mm2) and 39,850 M.Ohm (NYA 2.5 mm2). This shows that these cables have a better quality of sheath insulation resistance than others. While the cables that have the smallest sheath insulation resistance are 11,014 M Ohm (Sample B NYM cable 3 x 2.5 mm2), 10,720 M Ohm (Sample B NYM cable 2 x 2.5 mm2) and 21,580 M.Ohm (Sample A NYA 2.5 mm2) cable. According to PUIL 2000, the Minimum Value of Insulation on Electrical Equipment and Installation is: 1000 Ohms x Works Voltage. So the five samples of test cables meet the minimum limit of insulation resistance, which is 500,000 ohms, and are suitable for use for electrical installations in buildings as long as the works voltage don’t exceed 300/500 volts.